A Successful Percutaneous Endoscopic Gastrostomy Tube Feeding over Two Decades with No Complication: A Rare Case Report - Mandal, Amrendra (Cureus, 2019)
Percutaneous endoscopic gastrostomy (PEG) feeding is a common and widely performed procedure appropriate for long-term enteral nutrition in patients with multiple indications. We present the case of a 59-year-old woman with a PEG tube placed owing to complication following thyroid surgery approximately 20 years ago, representing the most extended duration of PEG tube feeding without any significant complication for chronic mechanical dysphagia. This case highlights the importance of PEG feeding, where this route can be used indefinitely in an appropriate clinical setting without complications. Interestingly, self-replacement of PEG tube was performed by the patient herself whenever she noticed clogging up of tube while self-feeding.